2016
DOI: 10.1002/2015gl067066
|View full text |Cite
|
Sign up to set email alerts
|

Outer radiation belt dropout dynamics following the arrival of two interplanetary coronal mass ejections

Abstract: Magnetopause shadowing and wave‐particle interactions are recognized as the two primary mechanisms for losses of electrons from the outer radiation belt. We investigate these mechanisms, using satellite observations both in interplanetary space and within the magnetosphere and particle drift modeling. Two interplanetary shocks/sheaths impinged upon the magnetopause causing a relativistic electron flux dropout. The magnetic cloud (MC) and interplanetary structure sunward of the MC had primarily northward magnet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
41
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 30 publications
(45 citation statements)
references
References 63 publications
4
41
0
Order By: Relevance
“…[]) or by nonlinear chorus interactions (see, e.g., the very recent study of this interval by Alves et al . []). Such loss processes are important topics for future study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[]) or by nonlinear chorus interactions (see, e.g., the very recent study of this interval by Alves et al . []). Such loss processes are important topics for future study.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, Alves et al . [] examined this extended depletion interval and suggested that loss at higher L shells ( L >5) was the result of magnetopause shadowing. At lower L shells (L ≲ 5) these authors suggested that the loss could plausibly be explained by either chorus wave losses or perhaps by ULF wave radial diffusion, although no direct modeling of either process was done.…”
Section: Introductionmentioning
confidence: 99%
“…While a further dedicated investigation should be undertaken, many of the shock-sheath structures discussed here have been studied recently for their strong effects on radiation belt electrons (for example, 1 and 8 October 2012 [Baker et al, 2013;Turner et al, 2014]; Hudson et al, 2014], 17 March 2013 [Boyd et al, 2014], 12 September 2014 [Alves et al, 2016], 17 March 2015 [Pierrard and Lopez Rosson, 2016;Li et al, 2016], and 22-25 June 2015 [Baker et al, 2016]). We have found that one of the conditions that makes shock-sheath structures geoeffective is a relatively steady southward B z upstream of the shock due to a preceding transient or preexisting southward IMF in the solar wind.…”
Section: Discussionmentioning
confidence: 99%
“…For 70% of the events (65/92), the magnetopause reached geosynchronous orbit (6.6 R E ). In Lugaz et al [], we discussed how the combination of large dynamic pressures and southward IMF behind shocks within transients can simultaneously compress and erode the magnetosphere, pushing the magnetopause down to below geosynchronous orbit and in some instances, resulting in electron losses through magnetopause shadowing [ Turner et al , ; Alves et al , ]. Enhanced wave‐particle acceleration and Dst effect [ Kim et al , ] are two other mechanisms which can contribute to energetic electron losses during this type of events [e.g., see Shprits et al , ; Kilpua et al , ].…”
Section: Studymentioning
confidence: 99%
“…If the flux rope has northward field, it can add to the depleting effect of the sheath, causing particularly long-lasting drop-outs of the high-energy electrons and magnetospheric quiescence (e.g., Alves et al 2016). Sustained southward field in the MC will in turn erode the magnetosphere, enhancing the electron losses at the magnetopause, but as the MCs have generally lower dynamic pressure and lower ULF wave power, the losses are not as pronounced as during the sheaths (Kilpua et al 2015a).…”
Section: Icmes/sheaths As Drivers Of Radiation Belt Electron Flux Varmentioning
confidence: 99%